Analisis Pemahaman Peserta Didik Sekolah Menegah Atas (SMA) Terhadap Konsep Trigonometri - Sugianto, Lis; Kriswinarso, Tri Bondan; Bachri, Saiful (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research is a type of descriptive research, aimed at describing and analyzing students' level of understanding of trigonometry concepts. The instrument used in this research was a test of the ability to solve valid trigonometry questions. Data collection was carried out by giving written tests in the form of descriptive questions. The sample for this research was class X MIA students at SMA Negeri 1 Bua, consisting of 40 people. The research process follows the following stages: (a) formulating a valid supporting instrument (test of ability to solve trigonometry questions), (b) collecting data to reveal students' understanding in solving the questions given, (c) analyzing data on students' understanding in solving questions, (d) discussing the results of the analysis, (e) drawing conclusions from the research results. The results of the research show: The ability level of class The average score of students' ability is 69.08 which shows that their ability is moderate with a standard deviation of 13.37 with the lowest score of 37.00 and the highest score of 92.00 from the ideal score of 100. The mode of 72.00 shows that the score most often obtained by participants education is 72.